Faktor-Faktor yang Mempengaruhi Intellectual Capital Terhadap Kinerja Keuangan pada Perusahaan Sub Sektor Hotel, Restoran dan Pariwisata yang Terdaftar di Bursa Efek Indonesia - Permatasari, Ulfi Nurindah; Andriana, Isni; Husni Thamrin, Kemas Muhammad (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the factors that can affect Intellectual Capital, using the variables Value Added Human Capital (VAHU), Value Added Capital Employee (VACA) and Structural Capital Value Added (STVA). The number of samples used in the study using the purposive sampling method were 22 companies in the hotel, restaurant and tourism sub-sector that were listed on the Indonesia Stock Exchange in 2018-2022. The type of data used is secondary in the form of published financial reports, and the data is analyzed using multiple linear regression analysis. The results of this study indicate that the variables Value Added Human Capital (VAHU), Value Added Capital Employee (VACA) and Structural Capital Value Added (STVA) have a significant effect on Net Profit Margin (NPM). Keywords: Value Added Human Capital (VAHU), Value Added Capital Employee (VACA), Structural Capital Value Added (STVA), Net Profit Margin (NPM)